Biblical narratives and human flourishing: knowledge through narrative - Stump, Eleonore; Wolfe, Judith (Routledge studies in analytic and systematic theology, 2024)
"Biblical narratives include some of the most important and influential narratives in human history, shaping human understanding of the most basic questions of human life as lived individually or in social association with others. These narratives have lasted for so many centuries because they offer deep insights into the nature of the human condition and human flourishing. This volume includes chapters by accomplished philosophers and theologians who bring their expertise to bear on biblical narratives to show the way in which each narrative contributes something distinctive to our understanding of human flourishing. They broaden the on-going work in analytic theology with a new focus on narrative and the knowledge of persons in philosophical-theological biblical exegesis. They also illustrate the narrative cognition that this methodology can provide. The book will be of interest to scholars of philosophy, theology, and biblical studies"